2015
DOI: 10.1111/1750-3841.13136
|View full text |Cite
|
Sign up to set email alerts
|

Multiphysics Modeling of Microwave Heating of a Frozen Heterogeneous Meal Rotating on a Turntable

Abstract: A 3-dimensional (3-D) multiphysics model was developed to understand the microwave heating process of a real heterogeneous food, multilayered frozen lasagna. Near-perfect 3-D geometries of food package and microwave oven were used. A multiphase porous media model combining the electromagnetic heat source with heat and mass transfer, and incorporating phase change of melting and evaporation was included in finite element model. Discrete rotation of food on the turntable was incorporated. The model simulated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The movement (rotation) of food product in domestic microwave oven has been simulated in several studies (Chen et al, 2014(Chen et al, , 2015Pitchai et al, 2015aPitchai et al, , 2015b using discrete rotational steps. Instead of continuous rotation, food products were assumed to be rotated discretely on turntables.…”
Section: Introductionmentioning
confidence: 99%
“…The movement (rotation) of food product in domestic microwave oven has been simulated in several studies (Chen et al, 2014(Chen et al, , 2015Pitchai et al, 2015aPitchai et al, , 2015b using discrete rotational steps. Instead of continuous rotation, food products were assumed to be rotated discretely on turntables.…”
Section: Introductionmentioning
confidence: 99%
“…2(c). Earlier research [30,41,44,45] work have showed an agreement of maximum rise in transient temperature at the central core region during continuous microwave heating. Therefore, it will be interesting and of direct utilities to understand the temperature distribution and thermal containment behavior of tissue phantom infused with dielectric nanoparticles compared to tissue without nanoparticles (W.N.P).…”
Section: Thermal Efficacy Of Nanoparticle Mediated Microwave Heatingmentioning
confidence: 81%
“…The conclusion could help properly determine the most significant parameters for a reliable model. Another porous material heating model by Pitchai et al [ 49 ] that simulated the rotational microwave heating of a heterogeneous sample (lasagna) was developed and validated. The heterogeneous lasagna sample with 6 layers, composed of meat sauce, pasta, ricotta cheese, pasta, meat sauce, and pasta from top to bottom layer, was used as a model food.…”
Section: Mechanistic Modelsmentioning
confidence: 99%
“…In addition to thermal profiles, in models that simulate the heating process of foods with high moisture or in small volume size, where the mass transfer can make a great difference to the final results, the moisture change due to the microwave power should also be validated. The total moisture loss [ 3 , 46 , 49 , 50 , 67 , 72 , 73 ] and/or transient point moisture content [ 74 ] have been measured for validation. Besides, the pressure generated due to moisture evaporation was also measured for validation [ 46 ].…”
Section: Mechanistic Modelsmentioning
confidence: 99%